Pembelajaran Bahasa Indonesia sebagai Media Edukatif dalam Mencegah dan Menanggulangi Bullying di Lingkungan SMP - Muthia Ayunda Br Situmorang; Nadya Syahla Athaillah; Nurliza Mawar; M. Surip (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the role of Indonesian language learning as an educational medium in preventing and addressing bullying in junior high schools. Bullying remains a serious issue as it not only causes physical harm but also affects students’ psychology, leading to loss of self-confidence, trauma, and disruption of the learning process. This research employed a qualitative approach with library research and content analysis methods. Data were collected through a review of journals, academic articles, online publications, and news sources related to bullying and character education. The findings indicate that Indonesian language learning plays a strategic role, not only as a means of communication but also as a medium for character building. Teachers can integrate moral values, ethics, and politeness in language use through teaching materials, discussions, and role-playing methods, enabling students to become more sensitive to humanity, empathy, and mutual respect. This implementation has proven effective in raising students’ awareness of the dangers of bullying while fostering positive behaviors in daily interactions. Therefore, Indonesian language learning can serve as an effective medium for preventing and overcoming bullying in the school environment.